2010
DOI: 10.1007/s10457-010-9341-8
|View full text |Cite
|
Sign up to set email alerts
|

Traditional perennial crop-based agroforestry in West Java: the tradeoff between on-farm biodiversity and income

Abstract: Agroforestry systems have been re-evaluated with a renewed scientific interest as appropriate models for achieving sustainable production while maintaining planned and associated biodiversity and agroecosystem functioning. Traditional bamboo-tree gardens in West Java are known to play substantial ecological and socioeconomic roles. In this study, we attempted to elucidate the relationship between income generation and biodiversity by studying 83 bambootree gardens that varied in species composition and degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Mixed tree gardens thus play a major role in the self-subsistence of farmers' households by supplying fuelwood (81 species), wood for housing construction (58 species), medicines (27 species) or fruit (38 species). These results confirm that complex agroforestry systems make a major contribution to the self-subsistence of rural households, as already identified in other tree-based systems in Indonesia (Christanty et al 1986;Michon et al 1986;Gouyon et al 1993;Brodbeck et al 2003;Okubo et al 2010). …”
Section: Importance Of Mixed Tree Gardens For the Local Populationsupporting
confidence: 88%
See 3 more Smart Citations
“…Mixed tree gardens thus play a major role in the self-subsistence of farmers' households by supplying fuelwood (81 species), wood for housing construction (58 species), medicines (27 species) or fruit (38 species). These results confirm that complex agroforestry systems make a major contribution to the self-subsistence of rural households, as already identified in other tree-based systems in Indonesia (Christanty et al 1986;Michon et al 1986;Gouyon et al 1993;Brodbeck et al 2003;Okubo et al 2010). …”
Section: Importance Of Mixed Tree Gardens For the Local Populationsupporting
confidence: 88%
“…In southeast Sumatra, the "jungle rubber" is another type of complex agroforestry system with high species diversity (268 plant species in a 1000 m² plot) and a structure similar to secondary forest (Gouyon et al 1993). In West Java, bamboo-tree gardens with high species diversity have been studied by Okubo et al (2010). Michon and de Foresta (1995) reported that villages in the island of Ambon were surrounded by agroforests that combined nutmeg and clove with fruit trees and forest nut trees.…”
Section: Complex Agroforestry Systems In Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…The density and diversity of various species were estimated by census survey on accompanied field excursions with agricultural A list of species in each agriculture fields, its purpose of usage and its annual production rate was recorded along with its specific agricultural niches/ land use type. Each species has a different yield cycle, so it is difficult to determine a standard/fixed system cycle (Rasul and Thapa, 2006;Okubo et al, 2010). Particularly of fruit or food tree species and older individuals are commonly replaced with new ones of the same or different species each year.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%